2012
DOI: 10.1007/s00223-012-9663-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Vitamin D Deficiency

Abstract: Vitamin D insufficiency and deficiency are widespread in many countries. We review the evidence pertaining to its prevention and treatment. Deficiency may be adequately treated with many different therapeutic regimens of either cholecalciferol or ergocalciferol, owing to the high therapeutic index of both compounds. Nevertheless, the current evidence suggests that regular dosing with oral cholecalciferol (e.g., 60,000 IU weekly) may have slight advantages over other regimens when replenishing vitamin D stores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…We also recommend starting with higher dosages to achieve serum levels above 30 ng/ml (75 nmol/l), followed by maintenance daily dosage of minimum 800-1000 IU (20-25 g) for breast or ovary cancer diagnosed women. • Administration: oral administration of vitamin D provides a faster and better controlled delivery compared with intramuscular preparations, since IM route leads to a sequestration in the muscle and fat with gradual release in the vascular system [65]. Vitamin D is fat soluble and because of this it is also advised to ingest it after the main meal of the day in order to improve intestine absorption [66].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…We also recommend starting with higher dosages to achieve serum levels above 30 ng/ml (75 nmol/l), followed by maintenance daily dosage of minimum 800-1000 IU (20-25 g) for breast or ovary cancer diagnosed women. • Administration: oral administration of vitamin D provides a faster and better controlled delivery compared with intramuscular preparations, since IM route leads to a sequestration in the muscle and fat with gradual release in the vascular system [65]. Vitamin D is fat soluble and because of this it is also advised to ingest it after the main meal of the day in order to improve intestine absorption [66].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…This could occur through stringent application of sunscreen, or active avoidance of the sun for presumed health reasons [50]. Women who cover themselves for cultural or religious reasons are at risk of vitamin D deficiency as well [51].…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…People with dark-colored skin who live far from the equator are at high risk of developing a vitamin D deficiency. However, there is also evidence that dark-skinned people can be at risk even in sunny climate such as Australia [50]. Age, gender, and race can be factors associated with risk of vitamin D deficiency.…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…In contrast to these findings Gallo et al [33] reported that 400 IU/day resulted in 25(OH)D levels > 75 nmol/L in 55% at 3 months and declined at 6, 9 and 12 months comparing supplementation with 400, 800, 1200 and 1600 IU/day during the first year of life. It was discussed whether the dose of vitamin D should be higher than 400 IU/day under those circumstances [34]. As suggested this might be due to non-adherence but also reflects the decreased relative intake of vitamin D per kilogram bodyweight -this is more significant in infants on 400 IU/day compared to infants on higher doses.…”
Section: Discussionmentioning
confidence: 99%